Clinical Characterization of Mucolipidoses II and III: A Multicenter Study - Alegra, Taciane; Sperb-Ludwig, Fernanda; Guarany, Nicole Ruas; Ribeiro, Erlane M.; Lourenço, Charles M.; Kim, Chong Ae; Valadares, Eugênia R.; Galera, Marcial Francis; Acosta, Angelina X.; Horovitz, Dafne Dain Gandelman; Schwartz, Ida Vanessa Doederlein (Journal of Pediatric Genetics, 2019)
Mucolipidoses (MLs) II and III are rare lysosomal diseases caused by deficiency of GlcNAc-1-phosphotransferase, and clinical manifestations are multisystemic. Clinical and demographic data from 1983 to 2013 were obtained retrospectively. Twenty-seven patients were included (ML II = 15, ML III α/beta = 9, ML III gamma = 3). The median age at diagnosis was 2.7 years. The predominant clinical presentations were skeletal symptoms. The ML II patients showed physical and cognitive impairment, while the ML III α/beta patients have more somatic abnormalities and usually were delayed in early development as compared with ML III gamma patients. This is the most comprehensive study exploring characteristics of Brazilian patients with MLs II and III.
Keywords: mucolipidosis II; mucolipidosis III α/beta; mucolipidosis III gamma